Prosedur Bongkar Muat Peti Kemas dari Kapal KM. Oriental Samudra pada PT. Salam Pacific Indonesia Lines Cabang Medan - Muhammad Wiraromatua Rangkuti; Suratni Ginting; Meriah Kita Deliani (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Container loading and unloading procedures are a series of essential operational activities carried out to systematically, safely, and efficiently move containers from ships to the stacking yard or vice versa. This study aims to examine these procedures, analyze the effectiveness of their implementation, and identify the obstacles and corrective efforts encountered in the field. The methods used include field observation (field research) and literature review (library research). The results indicate that the procedural stages involve document preparation (Bill of Lading and Manifest), ship berthing, the utilization of various loading and unloading equipment (such as Gantry Crane, RTG, and Headtruck), and container arrangement within the Container Yard (CY). The process involves three main work stages: Stevedoring, Cargodoring, and Receiving/Delivery, which require close coordination among port operators, foremen, and Stevedoring Workers (TKBM). Implementation can be hindered by crane breakdowns, headtruck limitations, traffic congestion, and slow stevedoring performance. Effective solutions suggested include routine equipment maintenance, increasing HT fleet capacity, enhancing human resource competency through training, and coordinating traffic routes with relevant authorities. Optimal procedure execution is crucial for ensuring smooth logistics flow, time efficiency, and occupational safety.